Navigating the Landscape of Small and Medium Size Enterprises in Lumbini Province, Nepal - Khatri, Bishnu Bahadur; Poudel, Chhavi Kiran; Pasa, Rajan Binayek (PYC Nepal Journal of Management, 2024)
Small and medium sized enterprises (SMEs) generate economy of the nation. This study explores navigating landscape of SMEs in Lumbini Province by analyzing its status, trends, opportunities, and challenges. Using an exploratory research design, data were collected through household surveys (n=130), FGDs (n=15), and KIIs (n=5), analyzed via the Resource-Based and Growth Pole models. The Province contributes 14.2% to national GDP through 68,492 SMEs, representing 16.8% of country’s total. SMEs in Lumbini are concentrated in districts bordering India, with agro-forestry enterprises being dominant, alongside significant contributions from tourism. Opportunities for growth SMEs include the involvement of returnee entrepreneurs, market access, modern technology, financial support, and the growing demand for organic products. Key challenges include limited technological support, financing issues, marketing difficulties, and regulatory constraints. The study emphasizes need for strategic interventions to enhance finance access, various support programs ensuring long-term growth of SMEs in Lumbini including other Provinces of Nepal.